¿Progreso social? Un análisis histórico-crítico de la medición en Colombia 2000-2018. - Sánchez Cárcamo, Ricardo Antonio; Cifuentes Sarmiento, José Alejandro (Revista Pensamiento Americano)
Introduction: This research presents a critical analysis of the conventional concept of social progress from different indicators with which Human Development, income inequality, quality and standard of living are recorded. Objective: In this way, it is intended to explain why, factually, a positive behavior of the conventional indicators of social progress in Colombia can be found, which is opposed to the evolution of the social conflict in terms of the social and trade union struggle, and to the increase in number of people arrested. Results and/or conclusions: The results suggest the need to establish an approach to the concept of social cohesion in the redefinition of social progress with the aim of overcoming the exposed methodological contradictions.